UPAYA PENCEGAHAN DAN PENANGGULANGAN TINDAK PIDANA TERORISME DI INDONESIA - Ahmad Syafii (Fakultas Hukum Universitas Muhammadiyah Palu, 2017)
Terrorism is a crime against civilization and one of the most serious threats to the sovereignty of each country. The crime of terrorism is done in anarchist ways that sacrifice innocent people. This crime is done in an organized and systematic way by involving networks between countries. Since the tragedy of September 11, 2001 in the United States, countries around the world have begun to step up their security and anticipatory measures against the terrorist movement, both coming from abroad and within the country itself. Tragedibom Bali I, on October 12, 2002, recorded 202 people killed and 300 people injured, Indonesia began to intensify the handling of terrorism. This is appreciated by the formation of Densus 88 Anti-Terrorism troops by POLRI Headquarters or other special forces whose main task is to anticipate and thwart terrorism in Indonesia. The Bali bombing case has forced the Indonesian government to issue Government Regulation in Lieu of Law No. 1 of 2002 on the Eradication of Criminal Acts of Terrorism and Perpu No. 2 of 2002 on the Implementation of Government Regulation Number 1 of 2002 which was then ratified by the House of Representatives with Law Number 15 Year 2003 and Law Number 16 Year 2003.Keywords : Prevention, Countermeasures, The Crime of Theorism